LEADERSHIP IN ISLAMIC EDUCATION: STUDY OF THEMATIC AL-QUR'AN AND AL-HADIST - Ikhwan, Afiful (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
The term leadership in Islam is associated with â€œthe highest leadership for Muslimsâ€, known as the Caliph, Imam, Imaratul and so forth. It means the supreme leadership for Muslims in religion and world affairs. The popular definition of the Caliphate is the supreme leader of the world in matters of religion replacing the Prophet Muhammad SAW. It is also called â€œReplacing the prophetic assignment to maintain and manage world affairsâ€. Of the supreme leader, and later expanded to all aspects of human life, to the smallest groups, families and individuals. In this case, of course we will not discuss the issue of caliphate, a succession of national leaders and so on, but we briefly cover how we should lead an institution or organization. Therefore, we need to figure out the feature of leaders, so that we can apply to choose a leader.